Propuesta para la implementación del Sistema de Gestión Integrado ISO 9001:2008 e ISO 17025:2005 en el Laboratorio de Producción de la Escuela Colombiana de Ingeniería Julio Garavito - Castro Osorio, Paula Alejandra; Ribero Fernández, Juan Sebastián (Escuela Colombiana de Ingeniería Julio Garavito, 2015)
Through the present work of degree a proposal is developed that establishes the criteria to implement an Integrated Management System taking as reference the norms NTC-ISO 9001: 2008 and NTC-ISO / IEC 17025, this last norm is focused to demonstrate the competences laboratory techniques. Given the above, the importance of supporting the management carried out by the Production Laboratory in all its areas of work and of contributing to the achievement of one of the purposes contemplated in the 2010-2020 development plan "Achieve recognition, accreditation and certification National and international". For the development of the proposal, the pertinent stages for the implementation of the SGI were defined; The defined sequence was: -Diagnosis -Planation -Design and documentation -Implementation -Tracking and improvement Once the sequence of implementation was defined and for the development of this work, three of the five stages were covered as indicated below: -Diagnostic: In this stage, a tool was developed and applied to evaluate the fulfillment of the requirements stipulated in the norms NTC-ISO 9001: 2008 and NTC-ISO / IEC 17025: 2005, the methodology of the five forces of Porter and a SWOT matrix was developed. -Planning: Normative and documentary correspondence was developed in order to identify the processes, procedures, documents and records (including technical records) required by the SGI. -Design and documentation: The documentation of the processes and procedure of the Production Laboratory was initiated, this work is carried out by contractors assigned by the Laboratory and by the Process Engineering Unit; the revision of the delivered documents is in charge of the Director of the Production Laboratory, the Process Engineering Unit and the authors of the degree work; In addition to the above, some additional documents required for the implementation of the SGI have been elaborated -The following stages of the implementation sequence will be in charge of the Production Laboratory or the person designated by the laboratory director. Finally, the conclusions and recommendations were established according to what was observed during the development of the degree work.

A través del presente trabajo de grado se desarrolla una propuesta que establece los criterios para implementar un Sistema de Gestión Integrada tomando como referencia las normas NTC-ISO 9001:2008 y NTC-ISO/IEC 17025, ésta última norma está enfocada a demostrar las competencias técnicas de los laboratorios. Dado lo anterior se observó la importancia de apoyar la gestión que realiza el Laboratorio de Producción en todas sus áreas de trabajo y de contribuir con el logro de uno de los propósitos contemplados en el plan de desarrollo 2010-2020 “Lograr reconocimientos, acreditaciones y certificaciones nacionales e internacionales”. Para el desarrollo de la propuesta se definieron las etapas pertinentes para la implementación del SGI; la secuencia definida fue: -Diagnostico -Planeación -Diseño y documentación -Implementación -Seguimiento y mejora Una vez definida la secuencia de implementación y para el desarrollo del presente trabajo se abarcaron tres de las cinco etapas como se indica a continuación: -Diagnóstico: En esta etapa se elaboró y aplicó una herramienta para evaluar el cumplimiento de los requisitos estipulados en las normas NTC-ISO 9001:2008 y NTC-ISO/IEC 17025:2005, se aplicó la metodología de las cinco fuerzas de Porter y se elaboró una matriz DOFA. -Planeación: Se elaboró la correspondencia normativa y documental con el fin de identificar los procesos, procedimiento, documentos y registros (Incluyendo registros técnicos) que requiere el SGI. -Diseño y documentación: Se inició la documentación de los procesos y procedimiento del Laboratorio de Producción, esta labor es adelantada por contratistas asignados por el Laboratorio y por la Unidad de Ingeniería de Procesos; la revisión de los documentos entregados está a cargo del Director del Laboratorio de Producción, la Unidad de Ingeniería de Procesos y los autores del trabajo de grado; adicional a lo anterior se han elaborado algunos documentos adicionales requeridos para la implementación del SGI -Las siguientes etapas de la secuencia de implementación estarán a cargo del Laboratorio de Producción o de la persona que el director del laboratorio designe. Finalmente se establecieron las conclusiones y recomendaciones de acuerdo a lo observado durante el desarrollo del trabajo de grado.
Keywords: Calidad; Sistemas de Gestión de la Calidad; Quality; Quality Management Systems